The International Students’ Experiences of Their Intercultural Communication Competence in Indonesia - Anfas, Muhammad Taufiqurrohman; Retnaningdyah, Pratiwi; Munir, Ahmad (LP. Ma'arif Janggan Magetan, 2023)
The study examined how, in the age of globalization, education had advanced to a new level where the sharing of information had transcended national boundaries and examined intercultural communication competency based on the experiences of foreign students in Indonesia. But educational establishments weren't completely equipped to meet these contemporary demands. Even though intercultural communication research is not new, concerns about emerging cultural diversity have only recently gained a lot of attention. As a result, intercultural communication competency (ICC) in educational sectors is still quite low and needs further investigation. The study used a descriptive qualitative methodology in conjunction with a case and phenomenological investigation strategy. Semi-structured interviews were used to collect the data, along with research material. Through the analysis of the interactive multicultural building model—which is bolstered by the ideas of intercultural communication and the internationalization of higher education—the research findings demonstrate the persistence of disparities and opinions, as well as an evaluation of the three-perspective model that serves as the main focus of the study. It consists of three processes: behavioral (intercultural adeptness), cognitive (intercultural awareness), and emotional (intercultural sensitivity). In addition, there are other difficulties that need to be overcome.